2016
DOI: 10.1039/c5bm00519a
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir-conjugated polymeric micelles prepared by RAFT living radical polymerization as a new active tumor targeting drug delivery platform

Abstract: Targeted drug delivery using polymeric nanostructures has been at the forefront of cancer research, engineered for safer, more efficient and effective use of chemotherapy. Here, we designed a new polymeric micelle delivery system for active tumor targeting followed by micelle-drug internalization via receptor-induced endocytosis. We recently reported that oseltamivir phosphate targets and inhibits Neu1 sialidase activity associated with receptor tyrosine kinases such as epidermal growth factor receptors (EGFRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Multiple functionalities using complex hydrophobic/hydrophilic polymeric structures prepared with highly controlled molecular weights and defined architectures are needed to enable self-assembled, stimuli-responsive regions (CO 2 , pH, and temperature) for triggered drug release and reactive groups for drug conjugation cross-linking and "click" chemistry. To this end, Kapishon et al 184 designed a specific smart chemotherapeutic delivery platform for active tumor targeting. They fabricated a new polymeric micelle-delivery system for active tumor targeting followed by micelle-drug internalization via receptor-induced endocytosis.…”
Section: Mechanism Limitationsmentioning
confidence: 99%
“…Multiple functionalities using complex hydrophobic/hydrophilic polymeric structures prepared with highly controlled molecular weights and defined architectures are needed to enable self-assembled, stimuli-responsive regions (CO 2 , pH, and temperature) for triggered drug release and reactive groups for drug conjugation cross-linking and "click" chemistry. To this end, Kapishon et al 184 designed a specific smart chemotherapeutic delivery platform for active tumor targeting. They fabricated a new polymeric micelle-delivery system for active tumor targeting followed by micelle-drug internalization via receptor-induced endocytosis.…”
Section: Mechanism Limitationsmentioning
confidence: 99%
“…Tamiflu ‐conjugated micelles also utilized for active targeted delivery of a hydrophobic chemotherapeutic agent such as doxorubicin and paclitaxel and found that polymer‐conjugated Tamiflu inhibit neuraminidase activity representing sialidase activity of Neu1 within the EGFR, and reduce the viability of PANC1 cells . So it exhibits dual functionality by exerting an anti‐tumour cell effect, and at the same time delivering and internalizing a hydrophobic chemotherapeutic anti‐cancer . Fe 3 O 4 @OA/ Tamiflu MNPs is also a promising candidate for anticancer drugs for use in targeted therapy …”
Section: Nanotechnology‐assisted Drug Deliverymentioning
confidence: 99%
“…38 To expand these targeted effects on the free enzyme, PANC-1 pancreatic cancer cells treated with soluble OP-pPEGMEMA conjugates in a dose-dependent manner achieved up to 45% reduction in cell viability. The OP-conjugated polymeric micelles specifically targeted Neu-1 similar to that of free OP.…”
Section: Polymeric Micelles: Receptor Targetingmentioning
confidence: 99%
“…The OP-conjugated polymeric micelles specifically targeted Neu-1 similar to that of free OP. 38 These OP-conjugated micelles targeting Neu-1 in complex with EGFRs provided a novel way of specific targeting and delivering chemotherapeutic agents by receptor-induced internalization of OPmicelles via Neu-1 binding.…”
Section: Polymeric Micelles: Receptor Targetingmentioning
confidence: 99%